Thermoelectric current in topological insulator nanowires with impurities - Erlingsson, Sigurdur I.; Bardarson, Jens H.; Manolescu, Andrei (Beilstein Journal of Nanotechnology, 2018)
In this paper we consider charge current generated by maintaining a temperature difference over a nanowire at zero voltage bias. For topological insulator nanowires in a perpendicular magnetic field the current can change sign as the temperature of one end is increased. Here we study how this thermoelectric current sign reversal depends on the magnetic field and how impurities affect the size of the thermoelectric current. We consider both scalar and magnetic impurities and show that their influence on the current are quite similar, although the magnetic impurities seem to be more effective in reducing the effect. For moderate impurity concentration the sign reversal persists.
Keywords: topological insulators, nanowires, thermoelectric current

(untitled) - Caballero-Calero, O.; Martín-González, M. (Scr. Mater., 2016)

(untitled) - Pennelli, G. (Beilstein J. Nanotechnol., 2014)

(untitled) - Gooth, J.; Gluschke, J. G.; Zierold, R.; Leijnse, M.; Linke, H.; Nielsch, K. (Semicond. Sci. Technol., 2015)

(untitled) - Bäßler, S.; Hamdou, B.; Sergelius, P.; Michel, A.-K.; Zierold, R.; Reith, H.; Gooth, J.; Nielsch, K. (Appl. Phys. Lett., 2015)

(untitled) - Peng, H.; Lai, K.; Kong, D.; Meister, S.; Chen, Y.; Qi, X.-L.; Zhang, S.-C.; Shen, Z.-X.; Cui, Y. (Nat. Mater., 2010)

(untitled) - Xiu, F.; He, L.; Wang, Y.; Cheng, L.; Chang, L.-T.; Lang, M.; Huang, G.; Kou, X.; Zhou, Y.; Jiang, X.; Chen, Z.; Zou, J.; et al. (Nat. Nanotechnol., 2011)

(untitled) - Dufouleur, J.; Veyrat, L.; Teichgräber, A.; Neuhaus, S.; Nowka, C.; Hampel, S.; Cayssol, J.; Schumann, J.; Eichler, B.; Schmidt, O. G.; Büchner, B.; Giraud, R. (Phys. Rev. Lett., 2013)

(untitled) - Cho, S.; Dellabetta, B.; Zhong, R.; Schneeloch, J.; Liu, T.; Gu, G.; Gilbert, M. J.; Mason, N. (Nat. Commun., 2015)

(untitled) - Jauregui, L. A.; Pettes, M. T.; Rokhinson, L. P.; Shi, L.; Chen, Y. P. (Nat. Nanotechnol., 2016)

(untitled) - Dufouleur, J.; Veyrat, L.; Dassonneville, B.; Xypakis, E.; Bardarson, J. H.; Nowka, C.; Hampel, S.; Schumann, J.; Eichler, B.; Schmidt, O. G.; Büchner, B.; Giraud, R. (Sci. Rep., 2017)

(untitled) - Erlingsson, S. I.; Manolescu, A.; Nemnes, G. A.; Bardarson, J. H.; Sanchez, D. (Phys. Rev. Lett., 2017)

(untitled) - Beenakker, C. W. J.; Staring, A. A. M. (Phys. Rev. B, 1992)

(untitled) - Staring, A. A. M.; Molenkamp, L. W.; Alphenaar, B. W.; van Houten, H.; Buyk, O. J. A.; Mabesoone, M. A. A.; Beenakker, C. W. J.; Foxon, C. T. (Europhys. Lett., 1993)

(untitled) - Dzurak, A. S.; Smith, C. G.; Pepper, M.; Ritchie, D. A.; Frost, J. E. F.; Jones, G. A. C.; Hasko, D. G. (Solid State Commun., 1993)

(untitled) - Svensson, S. F.; Persson, A. I.; Hoffmann, E. A.; Nakpathomkun, N.; Nilsson, H. A.; Xu, H. Q.; Samuelson, L.; Linke, H. (New J. Phys., 2012)

(untitled) - Svensson, S. F.; Hoffmann, E. A.; Nakpathomkun, N.; Wu, P. M.; Xu, H. Q.; Nilsson, H. A.; Sánchez, D.; Kashcheyevs, V.; Linke, H. (New J. Phys., 2013)

(untitled) - Sierra, M. A.; Sánchez, D. (Phys. Rev. B, 2014)

(untitled) - Stanciu, A. E.; Nemnes, G. A.; Manolescu, A. (Rom. J. Phys., 2015)

(untitled) - Zimbovskaya, N. A. (J. Chem. Phys., 2015)

(untitled) - Bardarson, J. H.; Brouwer, P. W.; Moore, J. E. (Phys. Rev. Lett., 2010)

(untitled) - Zhang, Y.; Vishwanath, A. (Phys. Rev. Lett., 2010)

(untitled) - Zhang, Y.-Y.; Wang, X.-R.; Xie, X. C. (J. Phys.: Condens. Matter, 2012)

(untitled) - Ilan, R.; de Juan, F.; Moore, J. E. (Phys. Rev. Lett., 2015)

(untitled) - Xypakis, E.; Bardarson, J. H. (Phys. Rev. B, 2017)

(untitled) - Arango, Y. C.; Huang, L.; Chen, C.; Avila, J.; Asensio, M. C.; Grützmacher, D.; Lüth, H.; Lu, J. G.; Schäpers, T. (Sci. Rep., 2016)

(untitled) - Bardarson, J. H.; Moore, J. E. (Rep. Prog. Phys., 2013)

(untitled) - Tserkovnyak, Y.; Halperin, B. I. (Phys. Rev. B, 2006)

(untitled) - Ferrari, G.; Goldoni, G.; Bertoni, A.; Cuoghi, G.; Molinari, E. (Nano Lett., 2009)

(untitled) - Manolescu, A.; Rosdahl, T. O.; Erlingsson, S. I.; Serra, L.; Gudmundsson, V. (Eur. Phys. J. B, 2013)

(untitled) - Chang, C.-H.; Ortix, C. (Int. J. Mod. Phys. B, 2017)

(untitled) - Müller, J. E. (Phys. Rev. Lett., 1992)

(untitled) - Ibrahim, I. S.; Peeters, F. M. (Phys. Rev. B, 1995)

(untitled) - Ye, P. D.; Weiss, D.; Gerhardts, R. R.; Seeger, M.; von Klitzing, K.; Eberl, K.; Nickel, H. (Phys. Rev. Lett., 1995)

(untitled) - Zwerschke, S. D. M.; Manolescu, A.; Gerhardts, R. R. (Phys. Rev. B, 1999)

(untitled) - Rickhaus, P.; Makk, P.; Liu, M.-H.; Tóvári, E.; Weiss, M.; Murand, R.; Richter, K.; Schönenberger, C. (Nat. Commun., 2015)

Handbook of Theoretical and Computational Nanotechnology - Nazarov, Y. V. (Quantum transport and circuit theory, 2005)

(untitled) - Stacey, R. (Phys. Rev. D, 1982)

(untitled) - Masum Habib, K.; Sajjad, R. N.; Ghosh, A. W. (Appl. Phys. Lett., 2016)

Transport in Nanostructures - Ferry, D. K.; Goodnick, S. M. (Cambridge University Press, 1997)

(untitled) - Wu, P. M.; Gooth, J.; Zianni, X.; Svensson, S. F.; Gluschke, J. G.; Dick, K. A.; Thelander, C.; Nielsch, K.; Linke, H. (Nano Lett., 2013)

(untitled) - Sánchez, D.; López, R. (C. R. Phys., 2016)

(untitled) - Sierra, M. A.; Saiz-Bretín, M.; Domínguez-Adame, F.; Sánchez, D. (Phys. Rev. B, 2016)

(untitled) - Torfason, K.; Manolescu, A.; Erlingsson, S. I.; Gudmundsson, V. (Phys. E (Amsterdam, Neth.), 2013)